Glycine protects the liver from reperfusion injury following Pneumoperitoneum - Saeedi, Mohammed al; Nickkholgh, Arash; Schultze, Daniel; Flechtenmacher, Christa; Zorn, Markus; Liang, Rui; Gutt, Carsten N.; Schemmer, Peter (European surgical research, 2018)
Background: Experimental pneumoperitoneum induces ischemia/reperfusion injury (IRI) in the liver, most likely via Kupffer cell (KC)-dependent mechanisms. Glycine has been shown to ameliorate IRI in various animal models. Thus, this study was performed to assess the effects of glycine on the liver after pneumoperitoneum. Materials and Methods: Sprague-Dawley rats (220-250 g in weight) underwent CO2 pneumoperitoneum (12 mm Hg) for 90 min. Some rats received i.v. glycine (1.5 mL, 300 mM) 10 min before pneumoperitoneum. Controls were given the same volume of Ringer’s solution. Transaminases, hepatic microcirculation, and phagocytosis of latex beads indexing both liver injury and KC activation were examined following pneumoperitoneum. Analysis of variance (ANOVA), plus a subsequent t test or χ2 test (or Fisher’s exact test) were carried out as appropriate. Results are presented as mean ± SEM. Results: Glycine significantly decreased lactate dehydrogenase at 1 h and both aspartate aminotransferase and alanine aminotransferase at 2 h after pneumoperitoneum from 477 ± 43, 154 ± 17, and 60 ± 6 U/L in controls to 348 ± 25, 101 ± 11, and 34 ± 3 U/L, respectively (p < 0.05). In parallel, glycine significantly decreased both the rate of permanent adherence of leukocytes to the endothelium by up to 35% and the rate of phagocytosis by > 50% compared to the control group. Conclusion: Glycine decreased IRI after pneumoperitoneum, most likely via KC-dependent mechanisms.
Gesehen am 07.05.2020